Sistem Pendukung Keputusan Pemilihan Maklon SkinCare Terbaik dengan Metode VIKOR - Resti Amalia; Ines Heidiani Ikasari; Perani Rosyani (ADA Research Center, 2024)
In the beauty industry, demand for skin care products is increasing, encouraging manufacturers to collaborate with other parties to produce products that suit consumers' needs and desires. The process of selecting a manufacturing loan partner or company that will produce skin care products is very important to ensure the quality and success of the product. In this research, we introduce the use of the VIKOR Method (ViseKriterijumsko Kompromisno Rangiranje) as an approach to selecting the best contracting partners in the skin care industry. The VIKOR method is one of the effective multi-criteria decision making methods, which allows the assessment of several conflicting criteria. We collect relevant criteria for selecting a maklon partner, such as product quality, price, production capacity, regulatory compliance and quality assurance. Then, we apply the VIKOR Method to rank each maklon partner based on these criteria. The results of this research provide recommendations regarding the best maklon partners who have the best balance between the various criteria considered. This approach can help skin care manufacturers to make more informed and optimal decisions in selecting manufacturing partners, thereby improving the quality and competitiveness of the skin care products produced. The final results showed that MPM Beuaty became the first best with a final score of 0 and the second best Pt.Bunga with a final score of 0.51.